2021
DOI: 10.4148/2378-5977.8032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Guanidinoacetic Acid, Creatine, and Choline on Protein Deposition and Creatine Status in Growing Cattle

Abstract: Objective: Objective: This study was conducted to evaluate effects of guanidinoacetic acid and creatine supplementation in the presence or absence of supplemental choline on body creatine status and lean tissue growth. Study Description: Study Description: Six ruminally-cannulated Holstein steers (321 lb) were utilized in an experiment consisting of six 10-day periods, where each steer received one of six treatments in each period. Treatments were abomasal infusion of a saline solution (control), 15 g/day guan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“… Ardalan et al (2021) observed no change in N retention when GAA was supplemented to steers extremely deficient in Met, but a tendency ( P = 0.10) for GAA to increase N retention was observed when 6 g/d Met was provided to steers. Using a research model similar to the current experiment, Grant et al (2021) observed increases in N retention when 15 g/d GAA was abomasally supplemented to growing steers, whereas Grant et al (2022) observed that abomasal infusion of 15 g/d GAA did not affect N retention. The similar nature of our study and those of Grant et al (2021 , 2022 ) makes the different responses hard to explain, although the improvements observed by Grant et al (2021) were not extraordinarily large.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“… Ardalan et al (2021) observed no change in N retention when GAA was supplemented to steers extremely deficient in Met, but a tendency ( P = 0.10) for GAA to increase N retention was observed when 6 g/d Met was provided to steers. Using a research model similar to the current experiment, Grant et al (2021) observed increases in N retention when 15 g/d GAA was abomasally supplemented to growing steers, whereas Grant et al (2022) observed that abomasal infusion of 15 g/d GAA did not affect N retention. The similar nature of our study and those of Grant et al (2021 , 2022 ) makes the different responses hard to explain, although the improvements observed by Grant et al (2021) were not extraordinarily large.…”
Section: Resultsmentioning
confidence: 50%
“…Using a research model similar to the current experiment, Grant et al (2021) observed increases in N retention when 15 g/d GAA was abomasally supplemented to growing steers, whereas Grant et al (2022) observed that abomasal infusion of 15 g/d GAA did not affect N retention. The similar nature of our study and those of Grant et al (2021 , 2022 ) makes the different responses hard to explain, although the improvements observed by Grant et al (2021) were not extraordinarily large. Several studies have evaluated the effect of feeding GAA on growth performance of finishing Angus bulls.…”
Section: Resultsmentioning
confidence: 50%